A kinetic study of the main guaco metabolites using syrup formulation and the identification of an alternative route of coumarin metabolism in humans - Gasparetto, Joao Cleverson; Peccinini, Rosangela Goncalves [UNESP]; Guimaraes de Francisco, Thais Martins; Cerqueira, Letcia Bonancio; Campos, Francinete Ramos; Pontarolo, Roberto (Public Library Science, 2015)
For decades guaco species have been empirically used for the treatment of respiratory diseases. However, studies have shown that the toxic and therapeutic effects of the main guaco metabolites are dose-dependent, and none clinical study was done to evaluate the behavior of these substances in humans. In this work, a pilot study measuring the kinetic profile of the main guaco metabolites was performed leading to the knowledge of an alternative route of coumarin metabolism in humans. Initial screenings demonstrated that the administration of 60 mL of guaco syrup (single dose) did not provide sufficient levels of coumarin (COU), 7-hydroxycoumarin (7-HCOU), o-coumaric acid (OCA) and kaurenoic acid (KAU). The pharmacokinetic parameters were calculated by orally administering 60 mL of guaco syrup spiked with 1500 mg of COU. The kinetic study demonstrated that the plasmatic levels of 7-HCOU (considered the main metabolite of COU) were 10 times lower than the levels of COU, and the kinetic profile of 7-HCOU suggests sequential metabolism in the liver with low access of 7-HCOU to the systemic circulation. The study also demonstrated that OCA is one of the main bioavailable metabolites of COU. Therefore, the hydrolysis of the lactone ring forming a carboxylated compound is one of the possible routes of COU metabolism in humans. The half-lives of COU, 7-HCOU and OCA were approximately 4.0, 1.0 and 3.0 h, respectively and there was evidence that the recommended dosage of guaco syrup did not provide sufficient levels of COU, 7-HCOU or OCA to obtain a bronchodilation effect. Clinical studies are necessary to prove the efficacy and safety of products based on guaco.